Alkyl Sulfides as Promising Sulfur Sources: Metal‐Free Synthesis of Aryl Alkyl Sulfides and Dialkyl Sulfides by Transalkylation of Simple Sulfides with Alkyl Halides. Issue 24 (27th November 2018) - Liu, Ting; Qiu, Renhua; Zhu, Longzhi; Yin, Shuang‐Feng; Au, Chak‐Tong; Kambe, Nobuaki
Abstract: A site‐selective metal‐free dealkylative approach to synthesize aryl alkyl and symmetrical dialkyl sulfides has been developed. This procedure is convenient and has wide functional group tolerance giving rise to sulfides carrying various alkyl chains from simple alkyl sulfides and alkyl halides in good to excellent yields. This transalkylation proceeds by an ionic mechanism via sulfonium intermediates and it was proposed that dimethylacetamide (DMAC) may participate in part to promote the reaction. Abstract : Site‐selective ! A metal‐free dealkylative approach to synthesize aryl alkyl and symmetrical dialkyl sulfides has been developed. This procedure is convenient and has wide functional group tolerance giving rise to sulfides carrying various alkyl chains from simple alkyl sulfides and alkyl halides in good to excellent yields.